Perioperative Anaesthesia Management Strategy for Multiple Major Surgeries : Case Report - Taufiq Gemawan; Teguh Prastyo; Eqiel Navadz Akthar Alami; Ridhotullah Istaz Maulana Suprapto; Adelia Handoko; Eko Aprilianto Handoko; Arsyzilma Hakiim; Sheilla Rachmania (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Major surgery lacks a universally clear definition. The European Surgical Association (ESA) defines it based on factors like patient comorbidities, procedure complexity, and clinical outcomes. Globally, surgery-related one-year mortality is about 5–6%, rising to 14% in frail patients. Laminectomy, laparotomy, and myomectomy is classified as major surgeries, each with significant risks such as bleeding, infection, and readmission. When combined, these surgeries require thorough anaesthesia management to ensure patient safety and surgical success. Objective: The purpose of this study was to give a deep understanding of the case, identify key issues and solutions, and present insight for future action. Methods: Data were collected through direct observation and patient medical records, covering the period from before surgery to three days post-operation. This included medical history, test results, and detailed treatment records. Results: Haemodynamic stability and intraoperative bleeding were well managed and anticipated. Careful repositioning was carried out, partly to maintain airway patency. The patient reported mild postoperative pain and was able to start sitting and walking exercises three days after the surgery. Conclusion: Patients undergoing multiple surgeries require careful monitoring and personalised anaesthetic management. Maintaining physiological stability, proper positioning, and effective fluid and pain control are key to preventing complications.